Benefits of tafamidis in patients with advanced transthyretin amyloid cardiomyopathy. (25th November 2020) - Rapezzi, C; Kristen, A.V; Gundapaneni, B; Sultan, M.B; Hanna, M
Abstract: Background: In the Tafamidis in Transthyretin Cardiomyopathy Clinical Trial (ATTR-ACT), tafamidis was shown to be an effective treatment for patients with transthyretin amyloid cardiomyopathy (ATTR-CM). Further assessment of the efficacy of tafamidis in patients with more advanced ATTR-CM would aid treatment decisions. Purpose: To characterize the benefits of tafamidis in patients with advanced ATTR-CM. Methods: In ATTR-ACT, ATTR-CM patients were randomized to tafamidis (n=264) or placebo (n=177) for 30 months. Efficacy outcomes included all-cause mortality and frequency of cardiovascular (CV)-related hospitalisations. Key secondary endpoints were change from baseline to Month 30 in 6MWT distance and KCCQ-OS score. Efficacy assessments in NYHA Class III patients at baseline (n=141) were a pre-specified analysis. In a post-hoc analysis, mortality and CV-related hospitalizations were assessed in all patients grouped into quartiles of increasing disease severity based on 6MWT distance at baseline. Longer-term all-cause mortality (as of 1 Aug 2019) was assessed in NYHA Class III patients utilizing data from ATTR-ACT patients who enrolled in a long-term, extension study (LTE) and continued treatment with higher dose tafamidis (n=55; median treatment duration 51.6 months); or, if previously treated with placebo, started tafamidis treatment (placebo/tafamidis; n=63 [50.1 months]). Results: In advanced ATTR-CM patients (NYHA Class III), tafamidis reduced the risk of death (HR [95% CI] 0.837, [0.541, 1.295], P=0.4253), and the decline in 6MWT distance (LS mean [SE], 31.6 (22.1) m; P=0.1526) and KCCQ-OS score (LS mean [SE], 13.1 (5.0); P=0.0090), vs placebo. Paradoxically, there was a higher frequency of CV-related hospitalizations with tafamidis (RR [95% CI] vs placebo, 1.411 [1.048, 1.900]). In all patients by 6MWT quartile, CV-related hospitalizations/year with tafamidis and placebo increased with disease severity, with the exception that placebo-treated patients in the highest severity quartile had fewer CV-related hospitalisations (0.73) than those in the third quartile (0.92). Mortality with tafamidis and placebo increased, and was greater with placebo, in every quartile (Figure). Survival (NYHA Class III patients in ATTR-ACT and LTE) was improved with high dose tafamidis with longer term follow-up (HR vs placebo/tafamidis [95% CI], 0.6569 [0.4175, 1.0336]; P=0.0692). Conclusions: These analyses, including longer-term follow-up, demonstrate that patients with advanced ATTR-CM benefit from tafamidis. The decrease in CV-related hospitalisations in more severe patients treated with placebo suggests that the comparatively greater hospitalisation frequency in NYHA Class III patients treated with tafamidis is a consequence of their lower mortality rate. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): This study was sponsored by Pfizer